Mechanochemical durability and self-cleaning performance of zinc oxide-epoxy superhydrophobic coating prepared via a facile one-step approach - Yap, Suk Wy; Johari, Norhasnidawani; Mazlan, Saiful Amri; Hassan, Noor Azlina (Elsevier Ltd, 2021)
Research efforts have intensified on developing superhydrophobic ZnO nanoparticle-based surfaces as they can impart desired hierarchical rough structures and properties. However, the widespread use of these surfaces is impeded by the limitations: complex fabrication procedures, weak adhesion, and limited durability performance. Most of these fabrication processes involved multiple treatment steps included the pre/post-treatment process to modify the textured surfaces. Herein, a convenient and effective one-step strategy is used to synthesis superhydrophobic ZnO-based coating with the introduction of both epoxy resin (EP) as the adhesive promoter and stearic acid (SA) as the low-energy modifier into an aqueous solution containing ZnO nanoparticles and ethanol via solution coating deposition method that binds all the components in a sole system. In the dense network, EP is responsible to render mechanical strength and coating-substrate adhesion, meanwhile, whereas SA functions to reduce the surface energy and preventing the EP to fully envelop the ZnO nanoparticles, thereby achieving a robust hierarchical rough structure, creating a layer of trapped air pockets. The resultant coating exhibits high water repellency, low water adhesion, and excellent self-cleaning ability with water contact and a sliding angle of 160.24° and 3°, respectively. Besides that, the superhydrophobic coating exhibited good mechanical durability after subjected to sandpaper-abrasion for a 20-m distance long and tape-peeling for 200 cycles. Furthermore, the coating still retained its superhydrophobicity after immersed in the corrosive bath with pH concentration ranged from 1 to 13 for 3 h, as well as the direct exposure to the temperature changes from 0 to 150 °C, manifesting its good chemical and thermal stability. This straightforward yet effective approach to develop a superhydrophobic coating with good durability and self-cleaning performance will inspire the scalable fabrication of multifunctional surfaces for practical applications in self-cleaning.